2018
DOI: 10.1097/spv.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

A Cost Analysis of Icon Reusable Underwear Versus Disposable Pads for Mild to Moderate Urinary Incontinence

Abstract: Objective The objective of this study was to perform a cost analysis assessing the economic feasibility of reusable underwear as alternative for disposable pads for women with mild to moderate urinary incontinence. Methods A consumer-perspective cost analysis was performed with the following assumptions: (1) consumers have mild to moderate urinary incontinence and use 2 pads per day (PPD); (2) consumers have a 2-week supply of underwear; (3) there is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The devices explored in the studies were as follows: female external urinary catheter, an external device used to manage urinary incontinence in a no‐invasive way in women without cognitive impairment, faecal incontinence, perineal wounds or even with menstruation (Beeson & Davis, 2018; Dublynn & Episcopia, 2019; Eckert et al, 2020; Fritsch et al, 2019; Mueller, 2019; Peters et al, 2021; Warren et al, 2021; Zavodnick et al, 2020); pads, disposable diapers or under‐pads used to manage both urinary and faecal incontinence in women and men (Grzybowska & Wydra, 2017; Gümüşsoy et al, 2019; Ostaszkiewicz et al, 2018; Sugama et al, 2012; Teerawattananon et al, 2015); mechanical devices, such as a continence dish, positioned to sit underneath the urethra, creating a support similar to the sub urethral sling, such as pessary or disposable intravaginal device, a single‐use and disposable device, which provide tension‐free support whenever the pressure is transferred from the abdominal cavity to the pelvic floor, or such as tampon (Farage et al, 2011; Lipp et al, 2014; Moore et al, 2021), a new prototype of underwear described as a pair of washable fixation pants with sewn‐in conductive threads that track where pads leak (Long et al, 2015), reusable underwear market for light incontinence (urinary leakage volumes up to approximately 25–30 ml daily), designed to be worn all day and machine washable (Alam et al, 2020), a new intelligent system pad, a system comprises of a urine collection cup made of medical‐grade silicone, a connecting hose between the urinal cup and the main body (Jeong et al, 2016). A summary of results is reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The devices explored in the studies were as follows: female external urinary catheter, an external device used to manage urinary incontinence in a no‐invasive way in women without cognitive impairment, faecal incontinence, perineal wounds or even with menstruation (Beeson & Davis, 2018; Dublynn & Episcopia, 2019; Eckert et al, 2020; Fritsch et al, 2019; Mueller, 2019; Peters et al, 2021; Warren et al, 2021; Zavodnick et al, 2020); pads, disposable diapers or under‐pads used to manage both urinary and faecal incontinence in women and men (Grzybowska & Wydra, 2017; Gümüşsoy et al, 2019; Ostaszkiewicz et al, 2018; Sugama et al, 2012; Teerawattananon et al, 2015); mechanical devices, such as a continence dish, positioned to sit underneath the urethra, creating a support similar to the sub urethral sling, such as pessary or disposable intravaginal device, a single‐use and disposable device, which provide tension‐free support whenever the pressure is transferred from the abdominal cavity to the pelvic floor, or such as tampon (Farage et al, 2011; Lipp et al, 2014; Moore et al, 2021), a new prototype of underwear described as a pair of washable fixation pants with sewn‐in conductive threads that track where pads leak (Long et al, 2015), reusable underwear market for light incontinence (urinary leakage volumes up to approximately 25–30 ml daily), designed to be worn all day and machine washable (Alam et al, 2020), a new intelligent system pad, a system comprises of a urine collection cup made of medical‐grade silicone, a connecting hose between the urinal cup and the main body (Jeong et al, 2016). A summary of results is reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…(Long et al, 2015). The acceptability of reusable underwear was investigated in terms of cost, findings suggested that the cost of reusable underweared are less than the cost of disposable pads with regular underwear (Alam et al, 2020). The acceptability was measured also in terms of comfort, appearance, size, position reliability, particularly the new prototype underwear was considered comfortable by more than 80% of participants and 93% of them found it easy to wash (Long et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been increased awareness among women regarding the use of reusable menstrual products due to not only cost savings, but also environmental savings 24 . Studies have shown that reusable incontinence products may be a satisfactory alternative for women 25,26 and may even be cheaper for women with mild incontinence symptoms 27 . With the creation of reusable incontinence products, more studies comparing cost and effectiveness between nonreusable and reusable products among varying severities of UI may produce a shift in product use which may help decrease financial hardship on incontinent women.…”
Section: Discussionmentioning
confidence: 99%
“…24 Studies have shown that reusable incontinence products may be a satisfactory alternative for women 25,26 and may even be cheaper for women with mild incontinence symptoms. 27 With the creation of reusable incontinence products, more studies comparing cost and effectiveness between nonreusable and reusable products among varying severities of UI may produce a shift in product use which may help decrease financial hardship on incontinent women. Additionally, studies investigating the underlying mechanism of economic disparities would be valuable in guiding health policies to improve equity in healthcare as well as incontinence product access and pricing.…”
Section: Discussionmentioning
confidence: 99%